Влијание на комбинираната примена на позитивен енд експираторен притисок и Тренделенбург положба врз успешноста и компликациите при ултразвучно водена транспекторална катетеризација на аксиларна вена кај пациенти на механичка вентилација - Саздов, Дарко (Медицински факултет, УКИМ, Скопје, 2019)
Introduction: Axillary approach to the central circulation is often used as an alternative to jugular and subclavian central venous catheterization when ultrasound is used. The use of ultrasound dose does not exclude occurrence of complications and does not guarantee 100% of success. The simultaneous use of Trendelenburg position and positive end-expiratory pressure increases the size of central veins. This study was conducted to evaluate and analyze the effect of simultaneous use of Trendelenburg position and positive end-expiratory pressure on the occurrence of mechanical complications and the success rate during ultrasound-guided axillary vein catheterization. Material and methods: This was a prospective randomized interventional study. We investigated 200 patients on mechanical ventilation admitted to our Intensive care unit. Patients were divided in two groups. Patients in the examined group (T+Peep 15 sm H2O) were placed in Trendelenburg position and peep of 15 cm H2O was applied. In the control group (T+zeep) patients were placed in Trendelenburg position and peep was not applied. In both groups axillary vein was catheterized with the use of direct ultrasound guidance. Patients’ characteristics age, gender, height, weight, vein size and depth, arteriovenous overlap, time needed, number of attempts, complications and success rate were recorded and followed. Results: Patients in both groups were homogenous regarding sex and age. In the examined group the success rate was 100% compared to the control group where the success rate was 95%. Arterial puncture occurred in 3 patients of the control group. Pneumothorax and hemothorax did not occur in both groups of patients. Time to cannulation and number of attempts were lower in the examined group of patients. The simultaneous use of Trendelenburg position and peep did not make statistically significant changes in MAP, and pulse rate, but resulted in better oxygen saturation in both groups of patients. Conclusion: The simultaneous application of Trendelenburg position and peep did not increase the risk of pneumothorax and hemothorax and at the same time resulted in increase of axillary vein size which can facilitate axillary vein catheterization and reduce complications.
Докторска дисертација одбранета во 2019 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Зорка Николова Тодорова.
Keywords: Trendelenburg position, positive end-expiratory pressure, axillary vein, ultrasound guidance